2000
DOI: 10.1093/jnci/92.1.54
|View full text |Cite
|
Sign up to set email alerts
|

Hematologic Disorders Associated With Primary Mediastinal Nonseminomatous Germ Cell Tumors

Abstract: In our study, approximately one in 17 patients with primary mediastinal nonseminomatous germ cell tumors was affected by a hematologic disorder, whereas no cases were seen among 334 patients with other extragonadal germ cell tumors. The hematologic disorder had a statistically significant impact on prognosis, with none of the 17 reported patients surviving for more than 2 years.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
139
3
9

Year Published

2000
2000
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 177 publications
(155 citation statements)
references
References 44 publications
2
139
3
9
Order By: Relevance
“…As first reported by Nichols et al, 25 associated syndromes such as hematologic malignancies (e.g., leukemia or myelodysplastic syndrome) may have an impact on prognosis. Hartman et al 26 reported that hematologic disorders occurred in 17 of 287 (5.9%) patients with mediastinal NSGCT, whereas no cases were seen in another 334 extragonadal NSGCT cases. In addition, NSGCT is occasionally associated with Klinfelter syndrome.…”
Section: Nsgctmentioning
confidence: 99%
“…As first reported by Nichols et al, 25 associated syndromes such as hematologic malignancies (e.g., leukemia or myelodysplastic syndrome) may have an impact on prognosis. Hartman et al 26 reported that hematologic disorders occurred in 17 of 287 (5.9%) patients with mediastinal NSGCT, whereas no cases were seen in another 334 extragonadal NSGCT cases. In addition, NSGCT is occasionally associated with Klinfelter syndrome.…”
Section: Nsgctmentioning
confidence: 99%
“…Furthermore, mediastinal nonseminomatous tumors are associated with Klinefelter's syndrome and hematological malignancy. 4,5) Cisplatin-containing chemotherapy dramatically improved the outlook for patients with GCT in the 1970s. The International Germ Cell Cancer Collaborative Group (IGCCCG) has proposed a staging classification based on prognostic factors for patients with metastatic GCT who were treated with cisplatin-containing chemotherapy.…”
mentioning
confidence: 99%
“…Accordingly, the presence of a mediastinal primary tumour in patients with nonseminomatous GCT was identified as a major adverse prognostic factor by the IGCCCG. Such patients appear to represent a clinically and biologically distinct disease entity (Nichols et al, 1985(Nichols et al, , 1987(Nichols et al, , 1990aHartmann et al, 2000b, (Saxman et al, 1994, Loehrer et al, 1998Hartmann et al, 2001a). Historically, the incorporation of cisplatin into chemotherapy regimens has yielded survival rates of approximately 30 -40% in retrospective analyses (Garnick et al, 1983;Logothetis et al, 1985;Delgado et al, 1993;Dulmet et al, 1993;Toner et al, 1991; International germ cell consensus classification, 1997).…”
Section: Discussionmentioning
confidence: 99%
“…As described before, there is approximately a 6% risk to develop a haematologic disorder in patients with primary mediastinal nonseminoma, which represents a biological phenomenon not related to chemotherapy (Nichols et al, 1985(Nichols et al, , 1990aHartmann et al, 2000b). The haematologic malignancies have a very aggressive clinical course with patients either dying before treatment, not responding to antileukaemic therapy, or achieving remissions of very short duration.…”
mentioning
confidence: 96%